A practical approach to scientific molding - Schiller, Gary F. (Hanser Publishers ; Hanser Publications, 2018)
"This easy-to-understand guide provides the necessary information to implement a scientific molding program. It is a hands-on reference for people on the molding floor, including those previously lacking theoretical background or formal education. The book covers how the injection molding machine prepares the plastic and understanding of plastic flow. The functions of the main machine components are explained and understanding of correct procedures and testing is developed. Each step of the process is clearly explained in a step-by-step manner, and simple examples of important calculations are provided. The practical approach is augmented by useful guides for troubleshooting and machine set-up. An Excel spreadsheet with a process test and a machine performance test is available as bonus material."--Resumé vydavatele